Condition assessment of shear connectors in slab-girder bridges via vibration measurements - Xia, Y.; Hao, Hong; Deeks, A.; Zhu, X. (American Society of Civil Engineers, 2008)
The paper presents a field study on condition assessment of the shear connectors in a full slab-girder bridge via vibration measurements. First, a model updating technique is employed to assess the condition of the whole structure, including boundary conditions, bearings, girders, slab, and shear connectors, from the accelerations on the slab measured in vibration testing. Then, a new damage index based on the difference of frequency response functions on the slab and the corresponding points on the girder is developed to evaluate the condition of shear connectors. The advantage of the new method lies in the fact that it does not need any reference data (undamaged data) for the structure. Compared with the results obtained using the model updating technique, the method is more reliable and accurate in assessing the condition of the shear connectors between the slab and girders. The effects of measurement noise on the damage identification results and the damage quantification are also studied through numerical simulation.